Rancang Bangun Private Cloud Storage Pada Dinas Koperasi & UKM Prov.Sumsel - Idrus, Muhammad Al; Mair, Zaid Romegar; Jambak, Muhammad Ikhwan (Jurnal Pengembangan Sistem Informasi dan Informatika, 2023)
The storage system that occurs in the Cooperative Office is still reasonably conventional. It is proven that storing and sharing files among employees still use Flash; it becomes a problem if the Flash occurs error / corrupt file then the stored file will be lost, and also vulnerable to viruses if the Flash is often connected to a computer then it takes a media/system that can store, share, or become a data center at the Cooperative Office. So, with this, the author has the idea to design private cloud storage using IaaS (Infrastructure as a Service). The test results show that the cloud storage system works well and is responsive. There are no significant lags in accessing the system, and the data transfer rate when saving files or sharing between employees is also satisfactory. The use of the cloud storage system also proved easy and intuitive for the staff and employees who took part in the trial. Implementing the Cloud Storage system at the cooperative and SME Office of South Sumatra province has successfully made centralized data storage for staff and employees in the environment. With this system, all personal and work-related data and Office archives can be accessed and stored efficiently